Implementasi Metode Al-Hisan Dalam Meningkatkan Pemahaman Makna AyatnPada Pembelajaran PAI Di Smp Al-MuslimnTambun Selatan - Muqit, Ade Abdul; Alawiyah, Tuti (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This study aims to determine how the Implementation of the Al-Hisan Method in Improving Understanding of the Meaning of Verses in Islamic Religious Education Learning at Al-Muslim Junior High School, South Tambun. In this study, the author used a qualitative method with data collection techniques through observation, interviews, documentation, and tests. The writing of the data uses descriptive qualitative, namely in the form of words, pictures, videos and not numbers. Based on the results of this study, the Implementation of the Al-Hisan Method in Improving Understanding of the Meaning of Verses in Islamic Religious Education Learning at Al-Muslim Junior High School, South Tambun ran smoothly and very well. The planning of Islamic Religious Education learning went well as desired and can be seen from the sample tests of students in each class. In its implementation, Islamic Religious Education teachers used three learning methods, namely the Lecture Method, Discussion and the Al-Hisan Method. In addition, this Al-Hisan method can help students' routine activities (tadarus along with the meaning of verses, kultum, and imtaq) and students' understanding of the meaning of verses continues to increase every year and is very helpful in Islamic Religious Education learning in distance learning conditions.